Pakistan and Central Asia: Understanding the Nature of the Evolving Relationship - Mr. Sajid Aziz (CISS Insight Journal, 2015)
Recent years have seen a greater level of interaction between Pakistan and Central Asian Republics (CARs). Mr. Nawaz Sharif, after assuming the office of Prime Minister, has officially visited all the member states of Shanghai Cooperation Organization (SCO) that includes all the Central Asian Republics with the exception of Turkmenistan. Leaders of the region have reciprocated in kind. These interactions have covered a whole gamut of issues: TAPI, CASA-1000, Pakistan’s offer to SCO members to use Pakistani Ports after the successful completion and operationalization of China-Pakistan Economic Corridor (CPEC) for the purposes of both exports and imports, etc. This paper seeks to understand the nature of this evolving relationship, its potential to increase regional connectivity and the concomitant benefits for stakeholders; and challenges in materialization of this vision in a precarious and turbulent regional context. These issues will be discussed in the broader context of other regional developments generally and the ‘Great Powers’ increasing interest in Central Asia, particularly.